A Proposed Model to Promote Teacher Leadership in Transforming Schools - Jaipian, Pornpisut (Scholar: Human Sciences, 2015)
The transformation approach to leadership is a broad- based perspective that encompasses many facets and dimensions of the leadership process (Northouse, 2007). Transformational leaders set out to empower followers and nurture them in change. They attempt to raise consciousness in individuals and to get them to transcend themselves for the sake of others. Transformation directly related to organization innovations (Jung, Chow, & Wu, 2003). Transformational leadership creates a culture in which members feel empowered and encouraged to fully discuss and try new things. Kouzes and Posner leadership model is employed as the main theoretical framework for this study (Kouzes and Posner, 2002). The five practices of leadership are: (1) Model the way, (2) Inspire and share vision, (3) Challenge the process, (4) Enable others to act, (5) and Encourage the heart. These five practices of exemplary leadership are deemed available to everyone and are not reserved for those with any ―special‖ ability. The model is not about personality it is about practice. Therefore the purpose of this inquiry is to identify the existing teacher leadership in transforming schools so as to purpose a model to promote such leadership elsewhere. The scope is set within Singburi Province in the central part of Thailand. The study is limited to elementary schools (N=127). The population of teachers is 1,499 members. Samples randomly selected are 306, significant at .05 levels (Krejcie & Morgan). A survey instrument was used to collect data regarding actual leadership of teachers. Scenario writing was used to gather evidence from each teacher as to what innovations he/she initiated successfully. In order to identify teachers with transformational leadership, the Multifactor Leadership Questionnaire (MLQ) was applied to the sample of teachers, (Bass & Volio, 1995). Thereafter, a scenario of successful innovations was collected from the identified ones. The findings lay bare that only 2.3 % of the samples were transformational leaders. The scenarios collected were content analyzed into subsets of the scope and framework of elementary educational programs in Singburi. The categories reflect the core culture of school, instruction, student development, quality assurance and the related supporting services, developmental activities for all school members and resource base. In accordance with the empirical findings, a model of teacher leadership in transforming schools is proposed. Discussions and recommendations are given for the use of this model in planning, implementing and evaluating instructional programs innovatively towards desired changes. The effective transformational teacher as a leader possesses an awareness of school curriculum trends, new approaches to organizing school, state-of-the-art instructional media and methodology, and research on improving student outcomes.